Textual Mirrors : Reflexivity, Midrash, and the Rabbinic Self - Stein, Dina (Book collections on Project MUSE., 2012)
In Textual Mirrors, Dina Stein draws on literary theory, folklore studies, and semiotics to closely examine midrashic tales in which self-reflexivity operates as a central element. Within these texts, rabbinic discourse itself becomes the object of reflection, both complicating and confirming its religious and ideological principles.